ATYPICAL CUTANEOUS PRESENTATION OF ADULT ONSET STILL DISEASE - Shah, Hammad; Achakzai, Humaira; Zuhaid, Muhammad (Journal of Ayub Medical College Abbottabad, 2016)
Adult onset still disease is a rare systemic inflammatory disease which presents with cardinal symptoms of spiking fever, arthralgia, and characteristic non pruritic evanescent salmon pink rash and neutrophilic leukocytosis. However it can have accompanied atypical cutaneous manifestations of pruritic plaques and papules. Clinicians need to be aware of this condition so that they can correctly diagnose it and prevent its serious complications. Keywords: Still’s Disease, Adult-Onset, Diagnosis, Young, Adult Female, Joint Diseases